Biosynthesis, characterization of Ag2O nanoparticles for enhancement of antioxidant and photo degradation activities - Tola Jabessa Masho; Meseret Melaku Ayane; Geremew Nigatu Endale; Shemelis Hailu Adula; Yadeta Dugasa Negasa; Bedasa Wagari Likasa; Tahir Safayo Mudda; Gemechisa Kebede Negari; Hika Chernet Amante; Sena Megersa Jida (Results in Chemistry)
Silver oxide (Ag2O) nanoparticles were synthesized via Biosynthesis methods using Croton macrotachyus leaf extract silver sulphate (Ag2SO4) was used as precursors and the extract was used in the reactions as reducing, stabilizing and capping agents which is a very easy and inexpensive synthesis method. Metal oxide nanoparticles characterized using UV–visible, TGA, Fourier transform infrared(FTIR),powder X-ray diffraction(XRD), X-ray photoelectron(XPS), and Scanning Electron Microscopy(SEM) with Energy Dispersive X-Ray(EDX) and Transmission Electron Microscopy(TEM), High Resolution Transmission Electron Microscope(HRTEM), and Selected Area Electron (SAED) which is used for determination of crystalline size, morphology,particle size and oxidation state with composition of elements in the sample. Metal oxide nanoparticles have a significant photo catalytic performance under visible light source confirmed that study supported Ag2O spherical structure, which exhibits enhanced photo catalytic activity and anti-oxidant activities as well as the size of the Ag2O nanoparticles was between 16 nm and 21 nm from the XRD(Scherrer equation),SEM & TEM) imaje software and Photo catalytic activity of Ag2O NPs were assessed against methylene blue (MB) dye degradation under natural sunlight illumination for 60 min. This sustainably photo degraded in direct solar irradiance with remarkable degradation percentage which is greater than 96.35 % and Scavenging activities Ag2O nanoparticles enhanced DDPH scavenging activities was 88 %